PROTOTIPE ALAT PENGHITUNG HARGA PADA PRINT-OUT ENGAN SENSOR WARNA TCS3200 SERTA SISTEM PENYIMPANAN DATA LOGGER - Muhammad Hariyanto; Mulkan Iskandar Nasution (JISTech (Journal of Islamic Science and Technology), 2022)
Research has been carried out aiming (i) to create a system and design a tool to calculate and add up the price of color and non-color printing, (ii) to determine the RGB frequency in determining a color, (iii) to find out the latest usage data in the Data Recorder program. The tool is designed to be able to calculate the type of concrete automatically, using the TCS3200 color sensor as a determinant of the type of mold with a 20x4 LCD display. The system uses the RTC DS1302 digital clock module, the SD Card Module for data storage as a function of the data logger program. The method applied in this research is the calculation method. This study uses international color measurement data as a frequency reference for the color sensor reading process, for the data logger program process using a PLX-DAQ (Parallax Data Acqusitions) program is an add-on to the parallax microcontroller data acquisition for Microsoft Excel. Making it easier to be able to unify tools in real time, by providing a color sensor calibration system program and storing data on an SD card (Data Logger) the results will be obtained, namely being able to distinguish color and colorless automatically with a tool success rate of 93.4% given a distance of 5 cm to the concrete paper.